Emissions of CO2 in Europe and the Asia–pacific region: Panel data model. (November 2022) - Filimonova, I.V.; Komarova, A.V.; Kuzenkova, V.M.; Provornaya, I.V.; Kozhevin, V.D.
Abstract: The rapid growth of CO2 emissions determines the problem of global warming, which has now become a severe threat to humanity. This work aimed to identify significant factors and assess their impact on CO2 emissions in Europe and the Asia–Pacific region using a panel data model. The authors have established the following factors' influence on CO2 emissions in European countries - GDP, consumption of fossil energy resources, population, urbanization, and in the Asia–Pacific countries - GDP, population, and "green factors". A positive coefficient before the GDP factor confirms the impact of economic growth on the amount of CO2 emissions. The authors also revealed that the "green factor" is not significant for European countries, since the development of alternative energy in Europe has reached the limit when the influence of the "green factor" significantly reduces emissions. However, for the Asia–Pacific region, as the largest region in terms of emissions, the "green factor" and the share of gas consumption had a negative impact on the dependent variable. Technological and institutional development of countries will be the main factor in determining competitiveness in international trade.